Manusia Penata Alam dan Bukan Penakluk Alam - Manggala Kala’tasik, Veronika Restu (Prodi Studi Agama-Agama, 2023)
Man was created with the mandate or responsibility to nurture another creation. The creation of the others in this regard is no exception to nature. Nature by not merely being created by the Creator but, through the realm of man, the glory of God is revealed. Man who is a noble creation is given the trust to keep nature and continue to declare the glory of God. Man must take good care of, maintain, work on nature. Man's covetousness of the beauty and richness of nature makes man